Examining the ontological and epistemological differences between evaluation and assessment in the education context - Chew-Hung Chang; Christina Ratnam-Lim; Wong Hwei Ming; Phoebe Ow; Joshua Wong Jia Hao (International Journal of Evaluation and Research in Education (IJERE), 2026)
In the field of education, assessment and evaluation (AE) are defining strategies for improving school practices with the overall goal of enhancing student outcomes. While AE is understood and considered by educators as two distinctly different domains, they are often used interchangeably among practitioners in the field. The aim of this paper is three-fold: to identify and clarify the epistemological and ontological differences between AE; develop operational definitions of AE that are transferable from research to classroom through a comprehensive literature review; clarify any misconceptions between the two domains, if any. A comprehensive meta-synthesis of literature from articles published in 32 journals between 2014 and 2024 revealed four frames to distinguish assessment from evaluation: i) information gathered; ii) methodology; iii) purposes and outcomes; and iv) stakeholders. To corroborate these conclusions, we also conducted a social lab which is based on the principle of the Delphi method with 11 participants. Additionally, insights from two social lab sessions revealed that apart from the ontological distinctions between AE, there were also epistemological distinctions. Eventually, three frames for exploring the difference between AE emerged from the data: ontology, epistemology, and stakeholders. By refining and developing this area of AE, the research hopes to contribute to a more informed and integrated educational landscape, encouraging further work in areas of AE.